Common pattern of gray-matter abnormalities in drug-naive and medicated first-episode schizophrenia: a multimodal meta-analysis. Issue 3 (25th October 2016) - Shah, C.; Zhang, W.; Xiao, Y.; Yao, L.; Zhao, Y.; Gao, X.; Liu, L.; Liu, J.; Li, S.; Tao, B.; Yan, Z.; Fu, Y.; et al.
Abstract : Studies of schizophrenia at drug-naive state and on antipsychotic medication have reported a number of regions of gray-matter (GM) abnormalities but the reports have been inconsistent. The aim of this study was to conduct multimodal meta-analysis to compare the cross-sectional voxel-based morphometry studies of brain GM in antipsychotic-naive first-episode schizophrenia (AN-FES) and those with antipsychotic treatment within 1 year (AT-FES) to determine the similarities and differences in these groups. We conducted two separate meta-analyses containing 24 studies with a sample size of 801 patients and 957 healthy controls. A multimodal meta-analysis method was used to compare the findings between AN-FES and AT-FES. Meta-regression analyses were done to determine the influence of different variables including age, duration of illness, and positive and negative symptom scores. Finally, jack-knife analyses were done to test the robustness of the results. AN-FES and AT-FES showed common patterns of GM abnormalities in frontal (gyrus rectus), superior temporal, left hippocampal and insular cortex. GM in the left supramarginal gyrus and left middle temporal gyrus were found to be increased in AN-FES but decreased in AT-FES, whereas left median cingulate/paracingulate gyri and right hippocampus GM was decreased in AN-FES but increased in AT-FES. Findings suggest that both AN-FES and AT-FES share frontal, temporal and insular regions as common anatomical regions to be affected indicating these to be the primary regions of GM abnormalities in both groups.